2007
DOI: 10.7326/0003-4819-146-6-200703200-00004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Intracranial Traumatic Findings on Computed Tomography in Patients with Minor Head Injury: The CHIP Prediction Rule

Abstract: The authors propose the highly sensitive CHIP prediction rule for the selective use of CT in patients with minor head injury with or without loss of consciousness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(179 citation statements)
references
References 35 publications
9
158
1
11
Order By: Relevance
“…Ghebrehiwet et al found the incidence as 17.2% in their study, 33.9% by Lee et al,7.6% by Smits et al, 58.3% by Zimmerman et al Stein et al calculated the incidence to be 17.2% 16 and Nagy et al as 3.3%. Variability of the incidence in work done by different authors is due the selection of patients, according to the clinical severity of the cases or random sampling or consecutive selection irrespective of clinical status.…”
Section: Intracranial Lesionsmentioning
confidence: 82%
“…Ghebrehiwet et al found the incidence as 17.2% in their study, 33.9% by Lee et al,7.6% by Smits et al, 58.3% by Zimmerman et al Stein et al calculated the incidence to be 17.2% 16 and Nagy et al as 3.3%. Variability of the incidence in work done by different authors is due the selection of patients, according to the clinical severity of the cases or random sampling or consecutive selection irrespective of clinical status.…”
Section: Intracranial Lesionsmentioning
confidence: 82%
“…Klinikinių studijų rezultatai patvirtina NOC ir CCHR kriterijų 100 proc. jautrumą, nustatant intrakranijinį pažeidimą, bet specifiškumas yra žemas [15,16,21,22].…”
Section: Sveikatos Mokslai / Health Sciences In Eastern Europeunclassified
“…Patienten mit stumpfen Verletzungen des Schädels werden zunächst als "leichtes SHT" kategorisiert, wenn im Rahmen der neurologischen Beurteilung 13-15 Punkte für die Glasgow Coma Scale (GCS) ermittelt werden. Allerdings zeigen bis zu 15% dieser Patienten in der kraniellen Computertomographie (CCT) eine zerebrale Lä-sion, etwa 1% müssen einer neurochirurgischen Intervention oder Operation zugeführt werden, 5-15% geben 1 Jahr nach dem Unfall noch Beschwerden an [2,3,6,7,9].…”
Section: Einführung Zum Themaunclassified